Bacterial Milk Quality along the Value Chain in Smallholder Dairy Production. (21st September 2022) - Washaya, S.; Jakata, C.; Tagwira, M.; Mupofu, T.
Abstract : This study aimed to evaluate the microbial quality of raw milk along the milk value chain at Africa University (AU). Eighteen Holstein-Friesian cows were used in this experiment. A total of 270 milk samples were collected for laboratory analysis at three different stages, during milking (DM), from the bulk tank (BT), and at the dining hall (DH), to determine the total bacterial count (TBC), Escherichia coli, and Salmonella enterica . Samples were cultured in Petri dishes using an appropriate medium for 48 hours. The plate count method was used to determine the quantity of bacteria. Data were analyzed using GLM SPSS. The results indicated that TBC increased (P < 0.05) from one site to the next along the value chain, yet it undulates when measured over time. Escherichia . coli and S. enterica counts increased (P < 0.05) at the last site of collection and the highest counts were recorded in week two. In conclusion, the current study indicates the hygiene of the dairy parlor with very low TBC, E . coli, and S. enterica counts during milking and bulk tank storage and that the relationship between TBC and E. coli is nonlinear with respect to time.